2017
DOI: 10.2215/cjn.03610417
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Patients with Cirrhosis and AKI Who Initiate RRT

Abstract: Background and objectivesLiterature on the prognosis of patients with cirrhosis who require RRT for AKI is sparse and is confounded by liver transplant eligibility. An update on outcomes in the nonlisted subgroup is needed. Our objective was to compare outcomes in this group between those diagnosed with hepatorenal syndrome and acute tubular necrosis, stratifying by liver transplant listing status.Design, setting, participants, & measurementsRetrospective cohort study of patients with cirrhosis acutely ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 48 publications
2
97
0
2
Order By: Relevance
“…5,6 The concept of AKI has been a major step forward in the diagnosis of acute impairment of kidney function in clinical practice and has stimulated research in this field. Some important new concepts have emerged from the research on AKI in cirrhosis in recent years, including; i) staging of patients with AKI in 4 different categories (1A, 1B, 2, and 3) that correlates with clinical outcomes; 6,7 ii) relevance of baseline serum creatinine in the prediction of outcomes; 8,9 iii) relevance of urinary output as an important prognostic factor in patients with AKI; 10 iv) outcome of renal replacement therapy in patients with AKI; 11 and v) identification of some kidney biomarkers able to establish with high accuracy the differential diagnosis between hepatorenal syndrome (currently known as HRS-AKI) and acute tubular necrosis (ATN). [12][13][14][15] Despite this important progress, some relevant questions related to AKI in cirrhosis still remain unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The concept of AKI has been a major step forward in the diagnosis of acute impairment of kidney function in clinical practice and has stimulated research in this field. Some important new concepts have emerged from the research on AKI in cirrhosis in recent years, including; i) staging of patients with AKI in 4 different categories (1A, 1B, 2, and 3) that correlates with clinical outcomes; 6,7 ii) relevance of baseline serum creatinine in the prediction of outcomes; 8,9 iii) relevance of urinary output as an important prognostic factor in patients with AKI; 10 iv) outcome of renal replacement therapy in patients with AKI; 11 and v) identification of some kidney biomarkers able to establish with high accuracy the differential diagnosis between hepatorenal syndrome (currently known as HRS-AKI) and acute tubular necrosis (ATN). [12][13][14][15] Despite this important progress, some relevant questions related to AKI in cirrhosis still remain unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…69 This was demonstrated by Allegretti et al who showed an 84% mortality at 6 months, with a mean survival of 21 days for patients, not listed for liver transplant, who developed hepatorenal syndrome and were started on dialysis. 70 Nephrologists should openly communicate to the patient and/or family if they feel RRT would be medically unbeneficial.…”
Section: Determining Who Is a Candidate For Rrtmentioning
confidence: 99%
“…50 It is worth noting that recent data showed a very poor prognosis in patients with cirrhosis and AKI not eligible for liver transplantation treated with RRT, regardless the indication was ATN-AKI or HRS-AKI (85% mortality at 6 months), thus, it may be futile in these patients. 89 Extracorporeal liver support systems have been used in the treatment of patients with ACLF (including those with HRS-AKI). The aim of these systems is to remove toxins such as bilirubin, bile acids, aromatic amino acids, and cytokines using an albumin dialysis-based technique.…”
Section: Management Of Acute Kidney Injury In Cirrhosismentioning
confidence: 99%